Influence of Synthesis pH on Textural Properties of Carbon Xerogels as Supports for Pt/CXs Catalysts for Direct Methanol Fuel Cells - C. Alegre; M. E. Gálvez; D. Sebastián; R. Moliner; M. J. Lázaro (International Journal of Electrochemistry)
Carbon xerogels (CXs) have been prepared by polycondensation of resorcinol and formaldehyde. Two synthesis pHs were studied in order to evaluate its influence on the electrochemical behaviour of Pt catalysts supported on previous carbon xerogels, synthesized by conventional impregnation method. Catalysts were also synthesized over a commercial carbon black (Vulcan-XC-72R) for comparison purposes. Characterization techniques included nitrogen physisorption, scanning electron microscopy, and X-ray diffraction. Catalysts electrochemical activity towards the oxidation of carbon monoxide and methanol was studied by cyclic voltammetry and chronoamperometry to establish the effect of the carbon support on the catalysts performance. Commercial Pt/C catalyst (E-TEK) was analyzed for comparison purposes. It was observed that the more developed and mesopore-enriched porous structure of the carbon xerogel synthesized at a higher initial pH resulted in an optimal utilization of the active phase and in an enhanced and promising catalytic activity in the electrooxidation of methanol, in comparison with commercial catalysts.